Expression of the long non-coding RNA H19 and MALAT-1 in growth hormone-secreting pituitary adenomas and its relationship to tumor behavior. Issue 67 (June 2018) - Lu, Tianyu; Yu, Chen; Ni, Hongbin; Liang, Weibang; Yan, Huiying; Jin, Wei
Highlights: The tumor size of invasive GHPAs was larger. The level of preoperative serum IGF-1 was significantly higher in invasive GHPAs. The expression of lncRNA H19 was significantly higher in invasive GHPAs. There was no significant differences between the expression of lncRNA MALAT-1 in invasive GHPAs and non-invasive GHPAs. Abstract: Aggressive growth hormone-secreting pituitary adenomas (GHPAs) represent an important clinical problem in patients with acromegaly. Surgical therapy, although often the mainstay of treatment for GHPAs, is less effective in aggressive GHPAs due to their invasive and destructive growth patterns, and their proclivity for infrasellar invasion. LncRNAs are important players in cancer development and emerging in various fundamental biological processes. In the present study, qRT-PCR was performed to examine the expression of lncRNA H19 and MALAT-1 in invasive and non-invasive GHPAs. Our results revealed that the expression of lncRNA H19 was remarkably higher in invasive GHPAs, however, there was no significant differences between the expression of lncRNA MALAT-1 in invasive GHPAs and non-invasive GHPAs, suggesting that lncRNA H19 may play an important role in GHPA invasion. LncRNA H19 might be a target for the study of GHPAs invasion, and a potential index for the diagnosis or prognosis of GHPAs.